Сравнительный анализ вегетативного обеспечения центральной гемодинамики и физической работоспособности единоборцев - Михалюк, Е. Л.; Михалюк, Євген Леонідович; Mikhalyuk, Ye. L (My University, 2016)
В даний час продовжує залишатися відстаючим розділ медико-біологічного забезпечення представників єдиноборств високого класу. У пропонованій статті зроблена спроба, на підставі відносно великого контингенту спортсменів, здійснити порівняльний аналіз інтегральних показників автономної нервової системи, центральної гемодинаміки і фізичної працездатності між тхеквондистами та боксерами високого класу. Результати порівняння свідчать про те, що ідентичний тренувальний процес з розвитком аналогічних фізичних якостей у представників даних видів єдиноборств однаково впливає на їх функціональний стан. Кореляційний аналіз показав головний взаємозв'язок, згідно з яким у тхеквондистів рівня МСМК збільшення PWC170/кг супроводжується зниженням СІ до величин, відповідних гіпокінетичному ТК, а у спортсменів рівня МС і КМС-I розряд –зниження індексу ІН – зменшенням СІ. У боксерів рівня МС і КМС-I розряд превалювання парасимпатичної ланки АНС супроводжується зниженням СІ до величин, відповідних економічно вигідному гіпокінетичному ТК. That the physical ability of an athlete to a large extent determined by the activity of the circulatory system, the level of functioning of which depends on the success of the reactions of adaptation to physical stress. Estimation of the cardiovascular and autonomic nervous system (ANS), in conjunction with the physical performance to determine current functional state of an athlete. At the present time continues to be lagging section biomedical support of representatives of martial arts high-end. In this article an attempt, based on a relatively large contingent of athletes, carry out a comparative analysis of integrated indicators of the autonomic nervous system, central hemodynamics and physical performance between taekwondo and high-class boxers. The comparison results show that the training process is identical with the development of similar physical qualities of the representatives of these martial arts are equally affect their functional status. Correlation analysis showed the main relationship, according to which at the level of world-class athlete thehkvondistov increase PWC170/kg followed by a decrease in SI to values corresponding gipokineticheskomu TK and MS-level athletes and CMS-I level - reduction of the index of regulatory systems tension - decrease in cardiac index. Boxers MS level and CMS-I rank prevalence parasympathetic ANS is accompanied by a decrease in SI to values corresponding to a cost-effective gipokineticheskomu TK. The data comparison between the integral indicators thekvondistami boxers and a qualification indicates that the training process is identical or similar physical developed at the same time, the same effect on their functional status.
Порівняльний аналіз вегетативного забезпечення центральної гемодинаміки та фізичної працездатності єдиноборців
Comparative analysis vegetative support of central hemodynamics and physical performance edinobortcev
Keywords: тхеквондо; бокс; варіабельність серцевого ритму; центральна гемодинаміка; фізична працездатність; кореляція; taekwondo; boxing; heart rate variability; central hemodynamics; physical performance; correlation